Behavioral Responses and Welfare Reform: Evidence from a Randomized Experiment - Robert Paul Hartley; Carlos Lamarche (Institute of Labor Economics (IZA), 2017)
Recent studies have used a distributional analysis of welfare reform experiments suggesting that some individuals reduce hours in order to opt into welfare, an example of behavioral-induced participation. Using data on Connecticut's Jobs First experiment, we find no evidence of behavioral-induced participation at the highest conditional quantiles of earnings. We offer a simple explanation for this: women assigned to Jobs First incur welfare participation costs to labor supply at higher earnings where the control group is welfare ineligible. Moreover, as expected, behavioral components and costs of program participation do not seem to play a differential role at other conditional quantiles where both groups are eligible to participate. Our findings show that a welfare program imposes an estimated cost up to 10 percent of quarterly earnings, and these costs can be heterogeneous throughout the conditional earnings distribution. The evidence is obtained by employing a semi-parametric panel quantile estimator for a model that allows women to vary arbitrarily in preferences and costs of participating in welfare programs.
Keywords: J22; I38; C21; C33; 330; welfare reform; quantile regression; panel data; program participation